Cyclic behaviour of soil-structure interfaces associated with modular-block reinforced soil-retaining walls. Issue 1 (2008) - Ling, H. I.; Wang, J.-P.; Leshchinsky, D.
Abstract : This paper describes the interaction behaviour of soil/geogrid and soil/concrete interfaces of a reinforced soil-retaining wall system under monotonic and cyclic loading conditions. A sand-clay mixture was tested with geogrids, which were manufactured from polyester and polyvinyl alcohol, and with concrete mortar in a modified direct shear device. In the cyclic tests, a total of 15 loading cycles or more were applied under constant displacement and by controlling the shear stress at a level of 56–74% of the monotonic shear strength. The test results showed that the strength of soil/geogrid interfaces was not affected significantly by cyclic loadings. At the end of cyclic loading, a larger stiffness and stress was mobilised in the reloading curve owing to the quasi-preconsolidated behaviour of the sand–clay mixture. For the soil/concrete interfaces, the interaction behaviour was different between the fresh and used (polished) specimens: significant strength reduction of up to 30% occurred in the used concrete specimens compared with the corresponding fresh specimens. The limited test results suggest that interface shear strengths obtained from monotonic loading may be relevant for designing reinforced soil-retaining walls subjected to earthquake loading.